HUBUNGAN PEMANFAATAN INTERNET SEBAGAI SUMBER BELAJAR DENGAN MOTIVASI BELAJAR BAGI SISWA DI SMA PLUS BINA BANGSA PEKANBARU - Damayanti, Tika Dwi; Johan, Rina Selva; Kartikowati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThe purpose of the study is to decribe the corelations of Internet usege as students’ learning device and motivation on social studies in the High School of Bina Bnangsa Pekanbaru. Samples were 53 students. Data was collected by using questionnaires, observation, and documentation; and data was analysed descriptively over the steps of scoring and tabulating, and then verified by formulation of product moment correlation. The independent variable was the internet utilization and motivation was variable Y. The results showed that the average student to respond frequently, meaning that students learn social studies demonstrate motivation when using the internet as a learning device. Through testing the correlation coefficient (r) is known that there is a relationship of 0521, and the coefficient of determination (r2) = 0.271 or 27.1%, meaning that the contribution of the use of internet learning resources to students' motivation is 27.1% while the rest is influenced by other factors. Testing the significance of correlation coefficient r can be seen from the calculation of t = 4607> table = 2.000. Based on the research result as described, it was suggested to the school principal to pay attention to the school internet facilities in order to support students’ learning activities as well as their motivation. Also suggested to teachers to be more focus on supervision over the usage of school internet facility..Keywords : Internet usage, Motivation, Social Sciences